Transcriptome Analysis Identifies Candidate Genes Related to Triacylglycerol and Pigment Biosynthesis and Photoperiodic Flowering in the Ornamental and Oil-Producing Plant, Camellia reticulata (Theaceae) - Yao, Qiu-Yang; Huang, Hui; Tong, Yan; Xia, En-Hua; Gao, Li-Zhi (Frontiers in Plant Science, 2016)
Camellia reticulata, which is native to Southwest China, is famous for its ornamental flowers and high-quality seed oil. However, the lack of genomic information for this species has largely hampered our understanding of its key pathways related to oil production, photoperiodic flowering process and pigment biosynthesis. Here, we first sequenced and characterized the transcriptome of a diploid C. reticulata in an attempt to identify genes potentially involved in triacylglycerol biosynthesis (TAGBS), photoperiodic flowering, flavonoid biosynthesis (FlaBS), carotenoid biosynthesis (CrtBS) pathways. De novo assembly of the transcriptome provided a catalogue of 141,460 unigenes with a total length of 96.1 million nucleotides (Mnt) and an N50 of 1080 nt. Of them, 22,229 unigenes were defined as differentially expressed genes (DEGs) across five sequenced tissues. A large number of annotated genes in C. reticulata were found to have been duplicated, and differential expression patterns of these duplicated genes were commonly observed across tissues, such as the differential expression of SOC1_a, SOC1_b and SOC1_c in the photoperiodic flowering pathway. Up-regulation of SAD_a and FATA genes and down-regulation of FAD2_a gene in the TAGBS pathway in seeds may be relevant to the ratio of monounsaturated fatty acid (MUFAs) to polyunsaturated fatty acid (PUFAs) in seed oil. MYBF1, a transcription regulator gene of the FlaBS pathway, was found with great sequence variation and alteration of expression patterns, probably resulting in functionally evolutionary differentiation in C. reticulata. MYBA1_a and some anthocyanin-speciﬁc biosynthetic genes in the FlaBS pathway were highly expressed in both flower buds and flowers, suggesting important roles of anthocyanin biosynthesis in flower development. Besides, a total of 40,823 expressed sequence tag simple sequence repeats (EST-SSRs) were identified in the C. reticulata transcriptome, providing valuable marker resources for further basic and applied researches on this economically important Camellia plant.